HUBUNGAN KEMAMPUAN METAKOGNISI DENGAN KEMAMPUAN MENULIS PARAGRAF DESKRIPSI SISWA KELAS X SMA NEGERI 2 PERBAUNGAN TAHUN PEMBELAJARAN 2012/2013 - MARIAH AL-QIBTIA (Universitas Negeri Medan, 2014)
This research was conducted to describe the relationship between the metacognition ability and the descriptive paragraph writing ability. It was done with observation about the decreation of descriptive paragraph writing ability. In this case showed that many aspects which related with student’s ability because writing activity included cognitive, afective, and psychomotor. Metacognition is the aspect which can help the students to set the three aspects. The sample’s research was 60 students of X class SMA 2 Perbaungan academic year 2012/2013. The instrument used was the metacognition scale and descriptive paragraph objective test. The result of this research showed that metacognition was significantly associated with the descriptive paragraph writing ability. It showed with r value was 0,895 on significance value 5%. While t value was 15,27 (value > t table = 1,67). The result of determination index was 80,1%. It means that the percentage of metacognition relation with writing ability was 80,1%. This result showed there is significantly positive relation between metacognition with descriptive paragraph writing ability.Keywords: Metacognition, writing, descriptive paragraph, relationship.